(untitled) (Research, Society and Development, 2020)
Optimal human performance depends on integrated sensorimotor and cognitive functions, both known to be extremely sensitive to sleep changes. The present study aims to verify the occurrence of sleep-related complaints in a sample of dizzy subjects and to compare the results of the vestibulometry among them. This is a cross-sectional observational research with a quantitative approach, conducted with subjects treated at a Balancing Outpatient Clinic of a University Hospital, submitted to Foam Laser Dynamic Posturography (sensory organization test and sensory analysis), Computerized Vectoelectronystagmography (oculomotor and vestibular tests) and the Dizziness Handicap Inventory (DHI) questionnaire to verify the handicap caused by dizziness. The sample consisted of 29 (20.14%) men and 115 (79.86%) women, with a mean age of 58.36 years. Of the total, 83 (57.64%) had a history of regular sleep (RS) and 61 (42.36%) had irregular sleep (IS). In posturography, there was a relationship between SI and lower values in positions II, III, IV and V, as well as with the vestibular system, in the sensory analysis. In vectoelectronystagmography the results point to normality of oculomotor function and vestibular reflexes, with rare indications of central alteration. DHI domains were significantly smaller in SI, indicating greater handicap caused by dizziness. These results confirm a high frequency of sleep-related complaints in this population, mainly affecting vestibular information, but not related to reflexes, but probably to the processing of upper vestibular information.